2015
DOI: 10.1371/journal.pone.0133363
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Microenvironment in Positive and Negative Sentinel Lymph Nodes from Melanoma Patients

Abstract: Melanomas are aggressive skin tumors characterized by high metastatic potential. Our previous results indicate that Natural Killer (NK) cells may control growth of melanoma. The main defect of blood NK cells was a decreased expression of activating NCR1/NKp46 receptor and a positive correlation of NKp46 expression with disease outcome in stage IV melanoma patients was found. In addition, in stage III melanoma patients, we identified a new subset of mature NK cells in macro-metastatic Lymph nodes (LN). In the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
10
0
4
Order By: Relevance
“…We also found that NK cells in SLN correlated with higher rate of relapses, supporting a tumor-promoting role of NK cells in SLN. 23 However, we also showed that metastatic lymph nodes contained NK subset CD56 bright CD16 C endowed with high lytic potential following activation by cytokines. 26 Depending of the disease stage localized or metastatic, lymph node NK cells may display different functions likely reflecting their recruitment from the tumor or their local activation.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…We also found that NK cells in SLN correlated with higher rate of relapses, supporting a tumor-promoting role of NK cells in SLN. 23 However, we also showed that metastatic lymph nodes contained NK subset CD56 bright CD16 C endowed with high lytic potential following activation by cytokines. 26 Depending of the disease stage localized or metastatic, lymph node NK cells may display different functions likely reflecting their recruitment from the tumor or their local activation.…”
Section: Discussionmentioning
confidence: 59%
“…We showed that NK cells infiltrated primary thick melanoma (more numerous in melanomas from aged patients) but their numbers did not impact survival. 23 In blood NK cells, we observed a progressive decrease of NKp46 expression level in patients with advanced melanoma and this alteration correlated with shorter duration of stage IV. 15 In addition, chemotherapy treated patients displayed distinct phenotypic modulations, 24 indicating that tumor progression and conventional chemotherapy may interfere with NK cell status in melanoma patients.…”
Section: Discussionmentioning
confidence: 63%
“…Few data are available on the prognostic value of the immunological status of the sentinel node, although several authors reported immunosuppressive changes occurring in the tumor-draining nodes [44,45,46]. We have recently observed that the transcriptional profiles of SNB of stage III patients distinguish melanoma patients with progressive disease [8], suggesting that the immunological setting in the SNB may anticipate the conditions of systemic immunity and provide prognostic information.…”
Section: Discussionmentioning
confidence: 99%
“…94,95 In primary tumors, NK cells are mainly found in the peritumoural margin and not in the tumor mass. 96 Recently, a unique NK cell population has been identified in metastatic lymph nodes, characterized by high CD56 and CD16 co-expression. These NK cells appear to lyse tumor cells more efficiently than blood-derived NK cells in the presence of IL-2 and IL-15.…”
Section: Innate Immune Cells Populations: Friend or Foe?mentioning
confidence: 99%